2007
DOI: 10.1021/ol701533d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Functionalized 3-Spiropyrrolizidine and 3-Spiropyrrolidine Oxindoles from Baylis−Hillman Adducts of Isatin and Heteroaldehydes with Azomethine Ylides via [3+2]-Cycloaddition

Abstract: A novel regioselective synthesis of a number of functionalized 3-spiropyrrolizidine and 3-spiropyrrolidine oxindoles from Baylis-Hillman adducts of isatin and heteroaldehydes via [3+2] cycloaddition of azomethine ylides in excellent yields has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…[11] MBH reactions are also "green" and highly atom efficient; they provide multifunctionalized derivatives have been used as for starting materials in the total syntheses of natural products, [12] heterocycles, [13] and drugs. [14] Despite the synthetic versatility, MBH reactions suffer from a serious drawback: for some substrates the reaction is very slow.…”
Section: Introductionmentioning
confidence: 99%
“…[11] MBH reactions are also "green" and highly atom efficient; they provide multifunctionalized derivatives have been used as for starting materials in the total syntheses of natural products, [12] heterocycles, [13] and drugs. [14] Despite the synthetic versatility, MBH reactions suffer from a serious drawback: for some substrates the reaction is very slow.…”
Section: Introductionmentioning
confidence: 99%
“…General procedure for synthesis of the 3,3′-dispiropyrrolidine bisoxindole (8a-l). A mixture of (E)-3-benzylideneindolin-2-one 7a-l (1 mmol), isatin (147 mg, 1 mmol), sarcosine (89 mg, 1 mmol) and anhydrous ZnBr2 (20%, 45 mg, 0.2 mmol) in methanol (10 mL) was sonicated for 30 minute at room temperature (25)(26)(27)(28)(29)(30) o C). After completion of the reaction as monitored by TLC, the mixture was poured in ice cold water and the precipitates were filtered and air dried.…”
Section: Methodsmentioning
confidence: 99%
“…The challenges associated with the synthesis of spiro-or dispiro-heterocycles containing the 3,3′-pyrrolidinyl-spirooxindole core have made them the subject of several elegant synthetic investigations. [22][23][24][25][26][27][28][29][30][31][32] Ultrasound irradiation has increasingly been used as a powerful tool for the preparation of organic molecules either in homogeneous or in heterogeneous liquid reaction systems. 33,34 The success and advantages of this method include shorter reaction time, higher yield, higher product purity, improved selectivity, reduced side product formation, and use of milder reaction conditions when compared with conventional heating.…”
Section: Introductionmentioning
confidence: 99%
“…(Table 1 In the literature survey we found that the tricyclic chromeno [4,3-b] pyrrolidine frameworks are known to be non-competitive antagonists of the muscular nicotin receptor. 12 It is well documented in literature that the Baylis-Hillman adducts have been utilized very well for the synthesis of various heterocyclic compounds. [13][14][15][16][17][18][19][20][21] We envisaged that the O-allylicmethoxy derivatives prepared from the Baylis-Hillman Chlorides.…”
Section: Antibacterial Activitymentioning
confidence: 99%